La formazione della costruzione impersonale in italiano - Giampaolo Salvi (Linguística : Revista de Estudos Linguísticos da Universidade do Porto, 2008)
In Modern Italian, one can identify two independent reflexive (“si”) constructions which syntactically demote the lexical subject: a passive one and an impersonal one, with quite distinct properties. Old Italian only had passive si – the impersonal construction is the result of many small changes in the rules and the domain of application of the passive construction: these changes began in the Old Italian period and lasted for at least five centuries. But this new construction, not being the result of a unitary project, continues to show signs of being imperfectly put together. In this case study, syntactic change consists of (a series of) small, local changes which are the result of chance (external causes) or are brought about by the possible imperfections of the linguistic system (internal causes)